PELATIHAN PENYUSUNAN LAPORAN KEUANGNA MELALUI PROGRAM MYOB ACCOUNTING DI KOPERASI UNIT DESA MULYOAGUNG, DAU, MALANG - Suryadi Suryadi; Edi Winarto; R. Setiawan; Ludfi Djajanto; Andi Asdani (Publisher UPT P2M Politeknik Negeri Malang, 2020)
This collaboration between Polytechnics and KUD administrators is one of the supports from academics to receive training in the preparation of cooperative financial reports, the results of dedication in this training are very useful. The method used by training and mentoring for the preparation & presentation of KUD financial statements is quite smooth. Broadly speaking, this training activity consists of Understanding Accounting Information Systems, Computer Accounting, Compiling Accounting Systems or Cycles and Presentation of Financial Statements through the MYOB Accounting Computing Program Package. The Covid pandemic period and the improvement of cooperative assets were a challenge for administrators to find and compile financial reports. Regarding new management activities, the practice of compiling and presenting financial statements has not been optimal and assistance will be carried out on an ongoing basis as long as necessary. This community service contribution has increased the knowledge and skills of cooperative management and has made hope for sustainability next year. The new management has implemented RAT and has a commitment to make improvements in totality in order to get an award that the Dau cooperative is still as good as it was 10 years ago, so that continuity of training can be planned.